The Effectiveness of Group Guidance Using the ABCDE Technique to Reduce Students’ Anxiety in Memorizing the Qur’an - As Syifa, Salsabila; Siregar, Alfin (Yayasan Sembilan Pemuda Indonesia, 2025)
This research aims to determine the effectiveness of group counseling services using the ABCDE technique in reducing students’ anxiety in memorizing the Qur’an at MTs Hifzhil Qur’an. Anxiety is one of the factors that can hinder the memorization process and reduce students’ motivation to learn. The ABCDE technique, which is part of the Rational Emotive Behavior Therapy (REBT) approach, is designed to help students identify and replace irrational beliefs that are the source of anxiety. This research employs a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research sample consisted of 20 eighth-grade students who were selected using purposive sampling techniques and divided into an experimental group and a control group. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis using a paired sample t-test showed a significant difference between anxiety levels before and after the intervention in the experimental group. The obtained significance value was 0.000 < 0.05, indicating that group guidance using the ABCDE technique is effective in reducing students’ anxiety in memorizing the Qur’an. These findings support the use of the ABCDE technique as a relevant psychopedagogical intervention in the context of religious education.